Strength Parameters of Clay Brick Walls with Various Directions of Force - Rafał Nowak (MDPI AG, 2021)
The study analyzes the anisotropy effect for ceramic masonry based on experimental tests of samples made of 25 × 12 × 6.5 cm3 solid brick elements with compressive strength fb = 44.1 MPa and cement mortar with compressive strength fm = 10.9 MPa. The samples were loaded in a single plane with a joint angle that varied from the horizontal plane. The load was applied in a vertical direction. The samples were loaded at angles of 90°, 67.5°, 45°, 22.5°, and 0° toward the bed joints. The most unfavourable cases were determined. It was observed that the anisotropy of the masonry significantly influences the load-bearing capacity of the walls depending on the angle of the compressive stresses trajectory. Approximation curves and equations for compressive strength, Young’s modulus, and Poisson’s coefficient were proposed. It was observed that Young’s modulus and Poisson’s ratio will also change depending on the trajectory of compressive stresses as a function of the joint angle. Experimental tests allowed to determine the failure mechanism in prepared specimens. The study allowed to estimate the masonry strength with the load acting at different angles toward the bed joints.